2010
DOI: 10.1128/jvi.00804-10
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4-Mediated Activation of p38 Mitogen-Activated Protein Kinase Is a Determinant of Respiratory Virus Entry and Tropism

Abstract: Respiratory viruses exert a heavy toll of morbidity and mortality worldwide. Despite this burden there are few specific treatments available for respiratory virus infections. Since many viruses utilize host cell enzymatic machinery such as protein kinases for replication, we determined whether pharmacological inhibition of kinases could, in principle, be used as a broad antiviral strategy for common human respiratory virus infections. A panel of green fluorescent protein (GFP)-expressing recombinant respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
146
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 50 publications
4
146
2
Order By: Relevance
“…Previous evidence indicated roles for p38 MAPK and ERK, in particular, in RSV infection (11,12,34). Our study demonstrated that RSV interferes with the p38 signaling pathway by spatially sequestering p38-P into viral IBs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous evidence indicated roles for p38 MAPK and ERK, in particular, in RSV infection (11,12,34). Our study demonstrated that RSV interferes with the p38 signaling pathway by spatially sequestering p38-P into viral IBs.…”
Section: Discussionmentioning
confidence: 67%
“…Previous work implicated the mitogen-activated protein kinases (MAPKs), in particular the extracellular signal-regulated kinase (ERK) and p38 MAPK, in the tropism as well as entry of RSV (10)(11)(12). The p38 MAPK is a central mediator involved in regulating cellular inflammatory and stress responses, as well as cellular protein synthesis (13,14).…”
mentioning
confidence: 99%
“…There have been many candidate cellular receptors described for RSV entry, including annexin II (70), CX3 chemokine receptor 1 (CX3CR1) (71,72), epidermal growth factor (EGF) receptor (73), calcium-dependent lectins (70), Toll-like receptor 4 (TLR4) (74,75), intercellular adhesion molecule 1 (ICAM-1) (76), nucleolin (77,78), and heparan sulfate proteoglycans (HSPGs) (79). Some receptors like EGF are purportedly used by only certain strains of RSV (73).…”
Section: Entry Of Rsv and Its Host Cell Receptorsmentioning
confidence: 99%
“…For RSV, our group has taken the approach of targeting specific aspects of host cell machinery that function as chokepoints of viral replication. Specifically, p38 mitogen-activated protein (MAP) kinase is a cell-signalling enzyme used by RSV during its replicative lifecycle [12], and we showed that treatment of cultured cells with a p38 MAP kinase inhibitor dramatically inhibited replication of several respiratory viruses (including RSV), without the drug causing overt cellular toxicity [13]. While these findings are intriguing, further studies are needed to extend our in vitro observations to the in vivo state.…”
mentioning
confidence: 79%